Dampak Pertumbuhan Ekonomi terhadap Ketimpangan Pendapatan dan Kemiskinan di Indonesia - Salsabila, Fadil; Azhar, Zul (Lembaga Yasin AlSys, 2023)
The VAR (Vector Autoregressions) model is one of the analytical models that can be used for time series data analysis. The VAR model in this study does not need to classify endogenous or exogenous variables in its analysis. The variables used in this research are economic growth, income inequality, and poverty. The purpose of this study was to determine the impact of economic growth on income inequality and poverty in Indonesia, the data used is annual data from 1996 to 2022. The stationarity test in this study shows that the data is not stationary at levels using the ADF (Augmented Dickey Fuller) test method. ) and the data shows stationary when the first differentiation is performed (First Difference). The results of the Johansen Test cointegration test show that the data is cointegrated or has a long-term relationship between variables so that the appropriate analysis model to use is the VECM (Vector Error Correction Model) model because the non-cointegration requirements are not met. The causality test was carried out using the Causality Granger method between variables showing that there is causality between the variables of economic growth and poverty.